Studi Deskriptif Faktor Produk, Harga, Tempat dan Promosi pada Produk Bedak Dingin Bunga Tanjung - Zaini, Muhammad; Muliyani, Muliyani; Isnani, Nazhipah; Wulandari, Ihya (Jurnal Kajian Ilmiah Kesehatan dan Teknologi, 2024)
The use of bedak dingin has been passed down from generation to generation by the people of South Kalimantan. Bedak dingin made from rice as the main ingredient is believed to make the skin smooth, brighten the skin, prevent and eliminate acne. This research aims to provide an overview of the application of the marketing mix concept which includes product, price, place and promotion for bedak dingin Bunga Tanjung in South Kalimantan. The research was carried out using a descriptive method where the samples used were women aged 17 – 45 years who live in South Kalimantan and have used bedak dingin Bunga Tanjung more than once. The instrument used was a questionnaire with five Likert scales. The sample collection technique is Accidental Sampling. Based on the Cochran formula, the sample size was 100 respondents. Data analysis was carried out with the help of Microsoft Excel in the form of percentage data presented in table form. The research results show that the product variable is dominated by the product indicator offered (75%), the price variable is the affordable price indicator (87%), the place variable is an easily accessible location (60%) and product promotions placed in the window (56%).